Concept of Nation State Building in Decisions of II Congress of Comintern - E. N. Emelyanova (Научный диалог, 2017)
The problem of nation state building is examined, which was actively discussed by the theorists of communism at the dawn of Soviet power. Great attention is paid to the work of The II Congress of the Communist International, meeting in 1920, during the Soviet-Polish war, when the creation of the new Plurinational state arose in the agenda. The novelty of the proposed research is in the fact that this problem has not yet been raised in the scientific studies. The peculiarities of the struggle of opinions in the Communist leadership on the national question and the geopolitical problems, which solving is still relevant today, are characterised. The author comes to the conclusion that the theoretical conclusions of the communists varied depending on the international situation. In 1920, during the “revolutionary offensive” the utopian idea of creating a World Soviet Republic and the establishment of the dictatorship of the proletariat was put forward. Later, with the final formation of the Versailles system, the Comintern advanced more moderate slogans, that in fact coincide with the program of world social democracy, peaceful coming to power through parliamentary elections and creation of a United States of Europe.